Exploring Typology of Residents Staying in Disaster-Prone Areas: A Case Study in Tambak Lorok, Semarang, Indonesia - Choirul Amin; S Sukamdi; R Rijanta (Universitas Muhammadiyah Surakarta, 2018)
Studies about population immobility, especially immobility associated with climate change-related disaster, are very limited. As a consequence, the explanation of population immobility in disaster prone areas is still blurred. This study contributes in explaining population immobility by exploring the typology of residents who did not move from disaster-prone areas. The survey was conducted towards the residents of Kampung Tambak Lorok Semarang, which is prone to three disasters simultaneously i.e. sea level rise, land subsidence, and tidal inundation. The study sample was 235 heads of households selected using proportional sampling area technique. Data were collected using a questionnaire consisting of two parts: (1) demographic, social, and economic characteristics of people who did not move from disaster prone areas; and (2) staying intention in disaster prone areas. Data analysis used descriptive analysis by using table and graph of respondent characteristic and relation between respondent characteristic and staying intention in research area. Three (3) typologies have been identified, namely: Type-1 are residents who wishes to stay; Type-2 are residents who still have not decided whether to stay or move; and Type-3 are residents who do not want to stay/want to move. Each of these typologies is described by place of birth, age, length of stay, education, occupation, and income. The understanding of the typology of residents living in disaster prone areas is important as inputs for policy-makers, especially regarding the relocation of people from disaster prone areas to be effective. The results of this study also contribute empirical evidence to the migration theory debate at the micro level, namely that the staying intention is a key element in the 'black box' of immobile decision-making from disaster prone areas.